Learning Outcomes of Sepak Sila Sepak Takraw Using Mosston's Teaching Style and Motor Ability Support - zulkifli Zulkifli; Rezki Rezki; Dea Ramadhini Ramadhini; Muhammad Rezki Alfindo Alfindo (Program Pascasarjana Universitas Negeri Jakarta, 2022)
The purpose of this study was to determine the difference in the effect of reciprocal teaching styles and teaching styles practice on learning outcomes of basic sepak takraw techniques seen from the differences in students' high and low motor ability. The research method uses an experimental method with a factorial design 2 x 2. The sample in this study amounted to 40 students who were divided into four groups (A1B1, A2B1, A1B2, A2B2) each group consists of 10 people. The results of the study stated that there was a difference in the effect of reciprocal teaching styles with practice teaching styles on the learning outcomes of sepak sila in groups of students who had high motor ability. There is a difference in the effect of reciprocal teaching styles with practical teaching styles on learning outcomes of basic sepak sila techniques in groups of students who have low motor ability. There is an interaction between teaching style and motor ability on student learning outcomes